Analisis Tingkat Kepuasan Mahasiswa terhadap Kualitas Belajar Mengajar Program Magister Akuntansi Terapan - Irsutami Irsutami (Politeknik Negeri Batam, 2012)
To measure the level of satisfaction of students of the Magister Akuntansi Terapan Universitas Gadjah Mada (MAKSI UGM) about quality of teaching and learning process, then the study of it done by spreading 90 questionnaires to students in the regular program of trimester I, II, III and BAWASDA. Measurement of the level of satisfaction had been designed to asking the student about perceptions and expectations of the dimensions of quality/customer satisfaction. The questionnaires are returned and completed by students as a respondent is 50 questionnaires. In General, the results showed that students feel quite satisfied of the quality of teaching and learning process that is given but there are several dimensions of quality/customer satisfaction should be attention by MAKSI UGM management to create greater levels of satisfaction.